Evaluación de crecimiento de rebrotes de Tectona grandis L. (TECA) en la Provincia de Guayas, Ecuador. - González Chávez, Luis Miguel (2020)
The objective of this research was to evaluate the quality of the teak sprout plantation in the company Tropibosques, SA located in the Balzar canton of the Guayas province. A completely randomized block design was used, where each sampling unit was in circular shape of 500 m2 with a radius of 12.62 m; located within the study area in order to avoid the edge effect, three data records were carried out at 9, 20 and 32 months, where the sampling units were established as treatments and the farms as repetitions (blocks), Through the growth parameters of the shoots (diameter, height, number of logs and straightness of the stem), an analysis of variance (ADEVA 2) was used, the quantitative variables showed significant differences between the three records, the best DBH of 0.122 m and height of 9.626 m belonged to the measurements made at the Alianza farm. According to the results obtained, the best volume of sprouts was the Alianza farm, followed by the Las Piedras farm and lastly the Hacha farm, while for costs, the establishment of a plantation by seed was evaluated, and it was compared with the maintenance costs of the shoots of T. grandis; being more profitable the management of shoots with 32% ($ 809.00), than the establishment of plantation by seed with 68% ($ 1,282.75).